The IMAGE beamline at the KIT Light Source - Angelica Cecilia; Rolf Simon; Elias Hamann; Marcus Zuber; Tomáš Faragó; Daniel Haenschke; Mathias Hurst; Thomas van de Kamp; Sondes Bauer; Rebecca Spiecker; Mateusz Czyzycki; Sergei Gasilov; et al. (Journal of Synchrotron Radiation, 2025)
The superconducting wiggler beamline IMAGE at the KIT Light Source is dedicated to full-field hard X-ray imaging applications in materials and life sciences, with a focus on high-throughput computed tomography, laminography experiments and systematic in situ and operando studies. With two experimental hutches, IMAGE provides space for its dedicated permanent experimental stations UFO-II and LAMINO-II as well as for flexible custom setups. IMAGE allows parallel beam imaging experiments in monochromatic, pink or white beam mode, with spatial resolutions ranging from ∼1 µm to ∼30 µm and a large horizontal and vertical field of view of up to 44 mm × 8 mm, respectively. Photon energies between 8 keV and 40 keV are provided by a double-crystal or double-multilayer monochromator optics with energy resolutions of 0.01% and 1.5–2.7%, respectively. The filtered white beam mode provides high flux densities of up to 7.5 × 1014 photons s−1 mm−2 at the sample position and energy spectra extending up to about 120 keV.